Dinâmica de transição da economia industrial para a economia do conhecimento e a utilização da inovação aberta no contexto brasileiro - Meroe, Giuliano Piccioni Silvestre de (2011)
Changes in economic scenarios, occasioned by the advent of information technology, and driven by the increasing pace of technological innovation, the socalled knowledge economy, puts knowledge as a decisive factor for the success of organizations in the principles of the XXI century. The new economy increasingly values the so-called intangibles - information, ideas, knowledge and intellectual production - which gives rise to organizations rethink their business models, adapting them to the demands of the new economic dynamics. The transition that we experience, challenges the assumptions of the industrial era, in which the measurement of success of organizations was based on the value of their property. Tangible goods are no longer the only reference value for organizations in the new context in focus. Organizations currently negotiating their intangible assets and leverage competitiveness through various components of intangible assets - intellectual property licensing, ownership of ideas and knowledge from outside organizations, externalization of their own ideas and internal knowledge. This picture of changes in contemporary society provides an environment for greater participation of stakeholders in the innovation process of organizations, and reflects an evolution in their business models to an open system, with more porous borders of organizations to the environment. The growing appreciation of the intangible capital - intangible assets, knowledge, ideas, intellectual property, etc. - and the use of IT tools are in two important vectors of the knowledge economy. The purpose of this study is to see whether companies that adopt a model within a collaborative logic, you get competitive advantage by becoming permeable to knowledge outside of their domain. Given this purpose, we will examine the concepts of innovation, will also be evaluated as the practice of a collaborative management model, proposed by Professor Henry Chesbrough, the scientist who coined the term open innovation. The implementation of this model, however, is linked to the organization's ability to strengthen its connections with other agents. For this reason, the study of social capital will be appropriate for this work because we see their relationship with this new management model. From this approach will be possible to understand that building a network of relationships between agents increases the fluidity in the exchange of knowledge, information and ideas among the participating actors. The interdependent relationship of support elements examined - the emergence of a new economy, intangible assets as the main component of value, capital, innovation, intellectual property - leads us to the conclusion that innovation is open on a model, potentially able to leverage competitive advantage for companies that fit into their busines models